Seroprevalence and Coinfections of Toxoplasma gondii in Childbearing Age Women in Turkey - I Akyar (Tehran University of Medical Sciences, 2011)
"nBackground: Our aim was to detect the rate of Toxoplasma gondii infections and the coinfections in childbearing age women in Turkey accompanying using seroprevalence data from a multicenter hospital setting."nMethods: Overal, 17751 childbearing age women through 16-45 years were included to the study between 2004 and 2010. The clinical samples of the patients were collected from 16 hospitals and medical centers mostly from Istanbul and three other cities from Turkey. Enzyme immunoassay tests were performed in our central laboratory in Istanbul to investigate T. gondii with other TORCH infections or Epstein Barr virus, Hepatitis B virus, Hepatitis C virus and Human Immunodificiency virus as accompanying infections."nResults: Among the tested sera 1.34% of the women were IgM and 24.61% were IgG positive for T. gondii. The coinfection rate was 3.36% among the IgM positive patients. CMV, EBV, HCV and rubella were detected as coinfections. IgM seropositivities of those infection agents were accepted as acute infection.  CMV and EBV were detected as 1.26% and HCV and rubella were detected as 0.42%."nConclusion: Turkish female population was found infected with T. gondii in high rates. Some of the seropositive patients also had accompanying CMV, EBV, HCV and rubella infections. Our aim was to detect Toxoplasma seropositivity and the accompanying infections with their rates. While coinfections worsen the situation unless they are detected, it is important to determine exact situation of the patient for the management of the therapy.